Single-Layer Differential-Fed Wideband Metasurface Antenna Using Characteristic Mode Analysis - Chao Huang; Chen-Jiang Guo; Yi Yuan; Xia Ma; Jun Ding (International Journal of Antennas and Propagation)
A single-layer differential-fed (DF) wideband metasurface (MTS) antenna is proposed in this paper. As the prototype, a three-by-three MTS formed by identical rectangular patches is investigated at first. We observe that there are many unwanted higher-order modes (HOMs) resonating near the wanted fundamental mode. Two probes with differential signals feed MTS on its centerline to suppress the majority of HOMs. The remaining HOM can be removed from the discussed frequency range by modifying the prototype MTS to a nonuniform structure. Then, the optimal feeding positions (FPs) are determined by a quantitative prediction of the impendence bandwidth (IBW) without any physical feeds involved. The processes of HOMs suppression and FPs determination are based on characteristic mode analysis with the virtual probes. Moreover, two interdigital capacitor plates are loaded on the probes to improve the impedance matching of the antenna. Finally, the proposed DF MTS antenna is fabricated and measured. The measured −10-dB IBW is 18.4% (4.93 to 5.93 GHz) with broadside radiation, stable high gains, and front-to-back ratios better than 21 dB.